Influence of a local short-term heat treatment on the formability of orbital formed functional components - Hetzel, Andreas; Merklein, Marion; Lechner, Michael (Procedia Manufacturing, 2021)
Conventional processes like shearing dispose a lack in efficiency and formability to manufacture functional components with a high geometric variety. A possibility to allow the efficient and sustainable manufacturing is the application of innovative forming operations like orbital forming. Thus, a strain-hardened component with a load-adapted thickness profile can be manufactured in a single-stage process. Thereby, the control of the material flow could be identified as major challenge due to the three-dimensional stress and strain state. In order to reduce the parts weight and simultaneously guarantee the same level of performance, conventional steel is substituted by lightweight materials such as precipitation hardenable aluminum alloys. However, new challenges arise due to the reduced formability of aluminum compared to conventional steel. In recent research, the potential of a short-term heat treatment to enlarge the formability could be shown. The presented process locally reduces the materials strength, thus allowing a control of the material flow by the interaction between softened areas and areas, which offer the initial conditions. In this contribution, the influence on the formability of orbital formed components manufactured out of the precipitation hardenable aluminum alloy EN AW 6016 by a local short-term heat treatment is investigated. Different geometry-based heat treatment layouts are applied in order to maximize the thickening on different radial positions. The potential to enhance the formability is evaluated by comparing geometrical and mechanical properties of the components manufactured in the conventional process route and with a previous heat treatment. The analysis of radial cross-sections and the hardness distribution reveals the positive influence of the heat treatment but also points out the geometrical dependency of the effect due to the characteristic material flow in orbital forming.<br
CRIS-Team Scopus Importer:2021-11-05
Keywords: Sheet-Bulk Metal Forming; Orbital Forming; Local Short-term Heat Treatment; EN AW 6016; Material Flow Control; Lightweight Design